State of Human Development: SAARC and Nepal - Poudel, Hom Nath (Economic Literature, 2016)
Human Development Index (HDI) is the strongest and widely used measure of overall performance of countries. The '2014 Human Development Report - Sustaining Human Progress: Reducing Vulnerabilities and Building Resilience' provides a fresh perspective on vulnerability and proposes ways to strengthen resilience. It highlights the need for both promoting people’s choices and protecting human development achievements. It takes the view that vulnerability threatens human development and, unless it is systematically addressed, progress will be neither equitable nor sustainable. Based on the light of this recent report launched on 24 July, 2014, here in this study, an attempt has been made to global highlights of the report, comparison of SAARC countries and remarks on the status of Nepal.Economic Literature Vol.12 2014: 50-55